Analisis Bibliometrik terhadap Penelitian Sejarah Perkembangan Bahasa Indonesia Tahun 2023–2025 - Ridwan Harun; Nurzaitunafia; Yohana Meria Delima; Yeremias Bardi; Karolus Gebi jawa (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
Research on the history and development of the Indonesian language has shown a significant increase in recent years, influenced by social dynamics, language policies, and digital transformation. However, systematic mapping of research trends, collaboration patterns, and thematic focus in this field remains limited. This study aims to analyze the development of research on the history of the Indonesian language during the 2023–2025 period using a bibliometric approach. The data were retrieved from the Dimensions database using the keyword History of Indonesian Language and were limited to journal articles published between 2023 and 2025. A total of 889 articles were selected for analysis. Bibliometric analysis was conducted using VOSviewer to visualize bibliographic networks, including country, institutional, journal, and author collaborations, as well as keyword co-occurrence. The indicators used in this study include the number of publications, citation counts, and total link strength. The results indicate that 2023 recorded the highest number of publications. Indonesia emerged as the leading country in terms of publication output and citation impact, while China, Germany, and the United States demonstrated strong academic collaboration networks. Keyword analysis revealed dominant themes related to language history, language policy, and linguistic dynamics within global and digital contexts. This study concludes that bibliometric analysis is an effective method for identifying research trends, directions, and collaboration patterns in studies on the history of the Indonesian language. The findings are expected to provide valuable insights for future research development and to support evidence-based language policy formulation.